Genome-Wide Association Study of Pelvic Organ Prolapse Using the Michigan Genomics Initiative. Issue 8 (August 2021) - Cox, Caroline K.; Pandit, Anita; Zawistowski, Matthew; Dutta, Diptavo; Narla, Goutham; Swenson, Carolyn W.
Abstract : Objectives: The aim of this study was to (1) replicate previously identified genetic variants significantly associated with pelvic organ prolapse and (2) identify new genetic variants associated with pelvic organ prolapse using a genome-wide association study. Methods: Using our institution's database linking genetic and clinical data, we identified 1, 329 women of European ancestry with an International Classification of Diseases, Ninth Revision ( ICD-9 )/ ICD-10 code for prolapse, 767 of whom also had Current Procedural Terminology ( CPT )/ ICD-9 / ICD-10 procedure codes for prolapse surgery, and 16, 383 women of European ancestry older than 40 years without a prolapse diagnosis code as controls. Patients were genotyped using the Illumina HumanCoreExome chip and imputed to the Haplotype Reference Consortium. We tested 20 million single nucleotide polymorphisms (SNPs) for association with pelvic organ prolapse adjusting for relatedness, age, chip version, and 4 principal components. We compared our results with 18 previously identified genome-wide significant SNPs from the UK Biobank, Commun Biol (2020;3:129), and Obstet Gynecol (2011;118:1345–1353). Results: No variants achieved genome-wide significance ( P = 5 × 10 −8 ). However, we replicated 4 SNPs with biologic plausibility at nominal significance ( P ⩽ 0.05): rs12325192 ( P = 0.002), rs9306894 ( P = 0.05), rs1920568 ( P = 0.034), and rs1247943 ( P = 0.041), which were all intergenic and nearest the genes SALL1, GDF7, TBX5, and TBX5, respectively. Conclusions: Our replication of 4 biologically plausible previously reported SNPs provides further evidence for a genetic contribution to prolapse, specifically that rs12325192, rs9306894, rs1920568, and rs1247943 may contribute to susceptibility for prolapse. These and previously reported associations that have not yet been replicated should be further explored in larger, more diverse cohorts, perhaps through meta-analysis. Abstract : Supplemental digital content is available in the text.